The Impact of Non-Performing Loans on Cooperative Profitability - Utami, Tri; Nisak, Sayida Khoiratun (CV. Zabags Qu Publish, 2025)
This study discusses the Kredit jamet. The purpose of cooperatives in extending credit is to increase profitability. The methodology of this study uses a descriptive quantitative approach. The sampling technique used is with saturated samples. Based on the results of the hypothesis test, it is known that the significance value is 0.024, which is smaller than 0.050 (0.024 < 0.050), and the calculation value is 2.384 > 2.045 t of the table. Therefore, it can be concluded that the bad credit variable has a significant effect on the profitability variable. So, Ho was rejected and Ha was accepted. The bad credit variable has a significant effect on the profitability variable. Based on the hypothesis test, bad loans have an impact on the profitability of the Srikandi Sukses Bersama Sharia Cooperative. Based on the results of the Coefficient of Determination test, it can be concluded that the influence of the bad credit variable on the profitability of the cooperative is 16.4%, the remaining 0.836% is influenced by other factors other than the variables studied.